2018
DOI: 10.1177/2378023118797550
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Racial Subjectivities and Ideologies in Brazil

Abstract: Census ethnoracial categories often reflect national ideologies and attendant subjectivities. Nonetheless, Brazilians frequently prefer the non-census terms moreno (brown) and negro (black), and both are core to antithetical ideologies: racial ambiguity versus racial affirmation. Their use may be in flux as Brazil recently adopted unprecedented race-targeted public policy. We examine propensities to self-classify as moreno and negro before and after the policy shift. Using regression modeling on national surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…While Afro Cutz is a pseudonym, the original name is in English and uses the word “Black” instead of preto . Paulo emphatically asserts preto has a racist connotation in Brazil, echoing the social science literature on race in Brazil (Bailey and Fialho 2018; Caldwell 2007). Throughout his explanation, there is a clear understanding of race relations in the U.S. and Black American culture.…”
Section: Conceiving a Communitymentioning
confidence: 95%
“…While Afro Cutz is a pseudonym, the original name is in English and uses the word “Black” instead of preto . Paulo emphatically asserts preto has a racist connotation in Brazil, echoing the social science literature on race in Brazil (Bailey and Fialho 2018; Caldwell 2007). Throughout his explanation, there is a clear understanding of race relations in the U.S. and Black American culture.…”
Section: Conceiving a Communitymentioning
confidence: 95%
“…However, recent studies have documented significant change in this status quo. In the informal realm, use of the notoriously ambiguous term moreno is declining, whereas use of the capacious term negro , promoted by the black consciousness movement, is growing (Bailey and Fialho 2018). Moreover, Brazilians are increasingly using official ethnoracial categories in open-ended identifications (Bailey et al 2018).…”
Section: Brazil’s New Racial Subjectivity and Opposition To Bolsonaromentioning
confidence: 99%
“…Regional variations are immense, from the Interior and the modernist architecture of its capital Brasília to more European influences in southern Brazil. With these regional variations come ethnic divisions, and, in fact, some studies have shown that Brazilians use over 100 self-reported ethnic terms and groupings to describe themselves (Bailey & Fialho, 2018;Harris, 1970;Telles, 2004). Still, the unifying idea of "being Brazilian," or Brasilidade, emerged in the postcolonial and slavery period in the early twentieth century of Brazil's history, as the sons and daughters of miscegenation were born in the country.…”
Section: Brasilidade and Brazilian Cultural Signifiersmentioning
confidence: 99%